2019
DOI: 10.1103/physrevb.100.195435
|View full text |Cite
|
Sign up to set email alerts
|

Large and controllable spin-valley splitting in two-dimensional WS2/hVN heterostructure

Abstract: Inspired by the profound physical connotations and potential application prospects of the valleytronics, we design a two-dimensional (2D) WS2/h-VN magnetic van der Waals (vdW) heterostructure and study the control of valley degree of freedom through the first-principles calculations. A considerable spin splitting of 627 meV is obtained at the K valley, accompanied with a strong suppression of that at the K' valley. An intrinsic large valley splitting of 376 meV is generated in the valence band, which correspon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…In which a large substantial valley splitting of 44 meV was predicted theoretically predicted in MoTe 2 /EuO [16], and the very recent experiment reported that the splitting efficiency in TMDs/EuS reached a value of 16 meV/T. 19 Additionally, to optimize the magnetic substrates, many 2D-magnets/TMDs vdW heterostructures have also been tried both experimentally and theoretically, such as CrI 3 /WSe 2 , 20,21 NiCl 2 /WTe 2 , 22 and h-VN/WS 2 , 23 where not only obtained considerable splitting size, but also verified the superiority of 2D/2D systems. More importantly, the reports further demonstrate that large interlayer charge transfer is a key factor in the formation of large valley splitting, which can enhance the magnetic proximity coupling between TMDs and magnetic substrates, and ultimately enlarge the valley splitting.…”
Section: Introductionmentioning
confidence: 90%
“…In which a large substantial valley splitting of 44 meV was predicted theoretically predicted in MoTe 2 /EuO [16], and the very recent experiment reported that the splitting efficiency in TMDs/EuS reached a value of 16 meV/T. 19 Additionally, to optimize the magnetic substrates, many 2D-magnets/TMDs vdW heterostructures have also been tried both experimentally and theoretically, such as CrI 3 /WSe 2 , 20,21 NiCl 2 /WTe 2 , 22 and h-VN/WS 2 , 23 where not only obtained considerable splitting size, but also verified the superiority of 2D/2D systems. More importantly, the reports further demonstrate that large interlayer charge transfer is a key factor in the formation of large valley splitting, which can enhance the magnetic proximity coupling between TMDs and magnetic substrates, and ultimately enlarge the valley splitting.…”
Section: Introductionmentioning
confidence: 90%
“…In C-1 configuration, the valley splitting is ~48 meV. Since one Bohr magneton is equal to 5.78 × 10 −5 eV T −1 , [ 53 ] the equivalent magnetic field is in the order of ~800 T for this system.…”
Section: Resultsmentioning
confidence: 99%
“…In close proximity to ferromagnets [21][22][23][24][25], the valley degeneracy of the TMD monolayer is lifted due to the broken time reversal symmetry (TRS), producing spin-splittings in the bands because of the competition between SOC and the induced exchange field. An enhanced valley splitting sensitivity to applied fields of up to 16 meV/T has been measured in a 2D WS 2 -EuS system [26], a giant valley splitting (300 meV) and sizable Rashba field ( 100 meV) are predicted for the commensurate MoTe 2 -EuO heterostructure [6,7], and giant valley splittings in WS 2 -VN [27].…”
mentioning
confidence: 88%